Socio-spatial logic of demolition and relocation in urban China - Zhe Lin; Gang Li (PLoS ONE, 2026)
While urban demolition ( Chai Qian ), a process encompassing housing removal and resident relocation, is a distinctive feature of China’s urban transformation, its underlying socio-spatial logic remains insufficiently understood. This paper extends Henri Lefebvre’s theory to examine the spatial patterns of demolition and their diverse driving routes. Using large-scale demolition data from five representative Chinese cities, a three-stage approach integrating spatial analysis, regression models, and text analysis identified a consistent “single hot core” pattern across all cities, shaped by network density, GDP, and population density. Road network and population density exerted location-specific influences, which indicates two dominant spatial logics: the renewal of dense, underdeveloped inner-city areas and the strategic preparation of well-connected zones for future development. GDP reinforced this dual logic. We proposed the Urban Demolition Complex Systems (UDCS) that conceptualizes demolition as a multi-scalar socio-spatial process shaped by interacting social, economic, and governance forces. This study provided a nuanced geographical perspective on the demolition process to illuminate how demolition operates as a spatially differentiated and policy-driven urban practice. In the context of rapid global urban transformation, our results help inform upstream, local government-level interventions to promote more equitable redevelopment strategies that support residents’ well-being and sustainable urban development.